A study on faciomaxillary injuries in a tertiary care hospital - G., Ravikumar; Manoharan, .; G. R., Sugapradha (International Surgery Journal, 2017)
Background: Faciomaxillary injuries are increasing in frequency and severity due to road traffic accidents and violence among the people of the delta districts of Tamilnadu. Alcohol plays a major role both in road traffic accidents and assaults resulting in faciomaxillary injuries. Human bites play a significant role in the soft tissue injuries of the face resulting in loss of lobule of ear, nasal tip loss and partial loss of lower lip. The purpose of this study was to evaluate the aetiology, incidence, patterns and treatment modalities of faciomaxillary injuries which include both soft tissue and bony injuries. Methods: The study was conducted in the Department of Plastic and Reconstructive Surgery of Thanjavur Medical College, Tamil Nadu, India between 2012-2015. About 850 patients in and around the delta districts of Tamilnadu admitted with various soft tissue and bony injuries of the faciomaxillary region were studied. Age, sex, time, mechanism and aetiology of injury, history of bleeding, unconsciousness and prior first aid, type of vehicle and use of preventive measures, type of fracture, associated injuries and treatment modalities were evaluated. Results: Faciomaxillary injuries were mostly due to road traffic accidents. Highest number of fractures was predominantly occurring in the age group of 21-30 years. Males incurred more fractures with a male to female ratio of 7.4:1.1. Fracture mandible was the most common followed by zygoma, nasal and naso ethmoid fractures. Pan facial fractures were more common among alcoholics. 28 patients had associated head injury and 14 patients had cervical spine injuries. Open reduction and internal fixation was the preferred modality for mandible whereas the mid face fractures were treated more often by closed methods. Soft tissue injuries involving ear, nose, lip and eyelids were more common. Conclusions: Drunken driving should be curbed in the society. Educating the people about road safety rules will bring down the faciomaxillary injuries. Motivating the public against violence will reduce human bites and soft tissue injuries of the face.